Enhancement and modulation of cosmic noise absorption in the afternoon sector at subauroral location (L = 5) during the recovery phase of 17 March 2015 geomagnetic storm - Behera, Jayanta K.; Sinha, Ashwini K.; Vichare, Geeta; Bhaskar, Ankush; Honary, Farideh; Rawat, Rahul; Singh, Rajesh (My University, 2017)
The present study has focused on the intense production of cosmic noise absorption (CNA) at Maitri, Antarctica (L = 5; CGM −62∘S, 55∘E) during the early recovery phase of the largest storm of the current solar cycle commenced on 17 March 2015 St. Patrick’s Day. The enhancement of CNA during 15–18 UT(14–17 magnetic local time (MLT); MLT = UT − 1 at Maitri) was as large as the CNA enhancement occurred during the main phase of the storm. During this time the CNA pattern also exhibits oscillation in the Pc5 (2–7 mHz) range and is in simultaneity with geomagnetic pulsations in the same frequency range. We observed the amplitude of CNA pulsation is well correlated with the level of CNA production. High-amplitude Pc5 oscillations were observed in the vicinity of auroral oval near Maitri. Absence of electromagnetic ion cyclotron (EMIC) waves is marked suggesting the possible role of VLF waves in precipitation. The reason for the intense CNA production is found to be the precipitation caused mainly by hiss-driven subrelativistic electrons. The CNA enhancement event is located well inside the dusk plasmaspheric bulge region as suggested by Tsurutani et al. (2015). Signature of enhanced eastward electrojet at Maitri during 14–17 MLT could be an additional factor for such large CNA. In order to establish the cause and effect relationship between the geomagnetic and CNA oscillations at Maitri, transfer entropy method has been used, which confirmed the modulation of CNA by geomagnetic pulsations.
Keywords: Geomagnetic pulsations; Geomagnetic storm; Cosmic noise absorption; Pc5 Ocillations